“Burning Candles at the Grave” Implementation of Christian Religious Education on the Tradition of Burning Candles at the Grave - Henderina Bathun, Victoria; Kolibu, Dirk Roy (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The phenomenon of respect for ancestors is as old as human civilization itself. This occurs due to the belief that deceased individuals can communicate God's will to those still living. A particular issue arises in the tradition of burning candles at graves, a practice believed to connect the living with their ancestors. The absence of this ritual is thought to bring adverse consequences for the community. Using descriptive qualitative methods and the theoretical framework of Ancestor Worship, this study examines the tradition of candle burning at graves. The objectives of this research are to explore the cultural and spiritual significance of the candle-burning tradition, identify its role in fostering ancestral respect, and assess its implications for religious practices, particularly among the Fatululi Carmel congregation in Kupang City. Additionally, the study seeks to analyze the potential for syncretism between traditional beliefs and Christian teachings. Research findings indicate that the Fatululi Carmel congregation performs this tradition on December 24th and 31st to strengthen relationships with ancestors, based on the belief in life after death. This practice reflects a perception that ancestors can contribute to a peaceful life for the community. The study highlights the Church's role in providing a Biblical perspective on such traditions through educational methods like Bible study classes, sermons, and cultural inculturation efforts. Furthermore, Christian Religious Education contributes to fostering faith, critical cultural awareness, and greater appreciation for cultural diversity while promoting tolerance and respect across traditions.